PERSEPSI MASYARAKAT TERHADAP ORANG DENGAN EPILEPSI TERKAIT MASALAH PERNIKAHAN - Arie Khairani, Lyna Soertidewi Kiemas, Fitri Octaviana, Herqutanto (NEURONA, 2012)
INTRODUCTION EPILEPSY AFFECTED APPROXIMATELY 50 MILLION PEOPLE WORLDWIDE AND EVEN IN THE ERA OF ADVANCED RESEARCHES AND EDUCATION ON EPILEPSY THE STIGMA STILL CAUSES A SERIOUS PSYCHOSOCIAL ISSUES